Recent Developments in Part-Time Work in EU-15 Countries : Trends and Policy - Hielke Buddelmeyer; Gilles Mourre; Melanie E. Ward (Institute for the Study of Labor (IZA), 2004)
A growing part-time employment share has been a main feature of a number of industrialized countries over the past two decades. A considerable variation in the rate of part-time work is evident by gender, age group, industrial sector and occupation. The stylized facts support the view that part-time employment represents an important opportunity particularly for young, older and female workers to enter the labour markets of the European Union. For the majority of workers in these groups, the decision to work part-time has been a voluntary one, which is all the more satisfactory in terms of welfare maximization. Our results indicate that the development of the part-time employment rate over time and the strong variation in the PTR across countries are significantly affected by policy and institutions. In particular policy measures geared toward encouraging part-time work are found to be positively related to actual part-time developments. These measures include both the legal framework directly affecting part-time positions and the creation of financial incentives (subsidies and improvement of social protection) to take up a part-time job. Moreover, other labour market institutions, including benefit systems and the stringency of employment protection legislation for regular contracts, are found to significantly but indirectly influence the growth in part-time work.
Keywords: J28; J21; J22; 330; part-time employment; labour supply; labour market policies; institutions; regulations; subsidies; Teilzeitarbeit; Arbeitsmarktpolitik; Arbeitsangebot; EU-Staaten